Discretionary Criminal Prosecution in Juvenile Proceedings - Ghazinyan, G.; Sujyan, T. (Bulletin of Yerevan University C: Jurisprudence, 2020)
An analysis of international juvenile justice requirements reveals the need to introduce alternative methods of solution of juvenile cases, including discretionary prosecution proceedings. The latter one will allow the juvenile to avoid undue trial as much as possible excluding also it`s possible negative impact. The article presents the domestic legislative regulations aimed at the implementation of the mentioned requirements, that is, the peculiarities of the application of coercive measures of educational nature, the existing gaps in the RA Code of Criminal Procedure and draft new Code of Criminal Procedure, and the possible ways of their improvement.